EFEKTIFITAS DANA PINJAMAN BERGULIR PROGRAM KOTAKU DI KECAMATAN BANYUDONO TAHUN 2016 - Dipa Nuswantara; Djuminah Djuminah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
PNPM or now called KOTAKU or cities without slumps is a program that aimed to reduce the poverty in Indonesia. One of KOTAKU’s program aimed to increase economic conditions of the poor. The revolving fund’s program purposed to provide poor people capital acces that expected could increase their economic aspect. Banyudono district has 15 villages this program recipient. There are 4 ratios to asses the efectiveness revolving fund that used by The Kementrian Pekerjaan Umum, they are : LAR, PAR, CCr, and also loaner from KSM’s women member. Results in this research that the LAR’s ratio averate value >20% which mean uneffective or Suspend. PAR’s ratio average value >20% which mean uaneffective or Suspend. CCr’s average value >125% which effective or satisfactory. ROI’s average value <0% or uneffective or Susepend. For the precentage loaner from KSM’s female member average value <50% which mean effective. Keywords: revolving loan funds; effectiveness; poverty; activity management unit.